Lean management and HRM practices in relation towards operational performance: a structural model - Azhani, Ismail; Yuserrie, Zainuddin (Universiti Malaysia Pahang, 2018)
This study examined the relationship between lean management and operational performance with the mediating effect of human resource management (HRM) practices in Malaysia local authorities. Participants reported their perceptions of lean management implementation (philosophy, process, people and partners, and problem solving), resultant operational performance (efficiency and effectiveness), and four dimensions of HRM practices: selection and hiring, training and development, performance evaluation, and rewards and incentives. The evaluation of structural model of Partial Least Square- Structural Equation Modeling (PLS-SEM) using SmartPLS3 showed the superiority of the models in which: (1) philosophy significantly and positively affected effectiveness performance, (2) rewards and incentives significantly affected both efficiency and effectiveness performances, (3) philosophy significantly and positively affected all the four dimensions of HRM practices, and (4) rewards and incentives mediate the relationship between philosophy and both efficiency and effectiveness performance. The implications of these results are discussed, especially regarding the effect of philosophy on operational performance in organization.